An innovative way of iodization of food products through the introduction of a new iodine-containing functional additives - Omelchenko, Christina V.; Polumbryk, Maksim O.; Litvyak, Vladinir V.; Batian, Anatoly N.; Kravchenkо, Viacheslav A. (Journal of the Belarusian State University. Ecology, 2018)
The complex formed by interaction between α-CD and/or β-CD and iodine has developed. It has found, that complex utilization in the human diet resulted in significant rise of urinary iodine excretion, and therefore, these compounds markedly improve iodine status of the humans. The additive can be promising for food fortification with iodine in modern ecological conditions.
Keywords: functional additive; iodine; iodination; cyclodextrins